Perinatal outcomes in pregnant women with hypertensive syndromes: An integrative review - Andréia Barcellos Teixeira Macedo; Liliana Antoniolli; Thayane Martins Dornelles; Leandro Augusto Hansel; Juliana Petri Tavares; Sonia Beatriz Cocaro de Souza (Universidade Federal de Santa Maria, 2020)
Objective: to verify the presence of psychosocial stress and resilience scores in nursing professionals who care for adults with multidrug-resistant germs. Method: cross-sectional study, carried out in an inpatient unit for adults, in a university hospital. The sample was intentional, composed of 39 nursing professionals, with data collected from January to May 2014 through the questionnaire Effort-Reward Imbalance and Resilience Score. Results: the mean age was 39.2 ± 9.0 years. It was observed that 69.23% (27) of the professionals had high psychosocial stress and 56.41% (22) low resilience. The correlation between psychosocial stress and resilience was r = 0.3 (p = 0.001). Conclusion: a high percentage of professionals with psychosocial stress and low resilience was identified, indicating a risk of psychoemotional and physical illness. This result reinforces the importance of reviewing the organization of work, encouraging the implementation of programs to increase resilience scores.